Design of Multiband Antenna Using Fractal and DGS Techniques (International Journal of Innovative Research in Engineering & Management, 2022)
A minkowski fractal antenna is designed  with a dimensions of substrate (27x27x1.6)mm3, patch of  dimensions (27x27)mm2 and ground plane of dimensions  (40x40)mm2 has been proposed with improved impedance  bandwidth and gains for wireless communication  applications.In this work, totally four types of antennas were  designed and mentioned. Four types of antennas mean one  is minkowski fractal antenna made by using microstrip patch  and works at three different set of frequencies (8.17GHz,  9.20GHz & 15.32GHz) with high gain which mainly covers  the applications of microwave frequency X-band and Ku  band. Secondly, the combination of fractal and DGS that  works at 11.5 GHz, which covers the applications of Ku  band. The third design is DGS and works at dual set of  frequencies (2.4 GHz & 5.25 GHz) and which mostly covers  the major applications of WLAN, S-band frequency. Finally,  the fourth design is plus shaped DGS works at multiple set  of frequencies (13.73GHz ,15.50GHz,18.18GHz,21.04GHz)  which mainly covers the major applications of K-band and  Ku-band frequencies.
Keywords: Defected Ground Structure; frequency; gain; minkowski fractal antenna